HUBUNGAN ANTARA USIA IBU HAMIL DENGAN KEJADIAN ABORTUS HABITUALIS DI RSUD ULIN BANJARMASIN PERIODE TAHUN 2010-2013 - Kismiliansari, Desy Elisa; Nizomy, Ihya Ridlo; Budiarti, Lia Yulia (Jurnal Berkala Kedokteran, 2015)
Recurrent miscarriage is an abortion that occurs two or more times in a row before 20 weeks of gestation. Motherâs age is a cause of recurrent miscarriage. The aim of this study is to determine the relation between motherâs age and the incidence of recurrent miscarriage on outpatient clinic and delivery room patients at Obstetric and Gynecologic Department of Ulin General Hospital Banjarmasin from 2010 to 2013. This study used analytic observational method with retrospective approach, the motherâs age was divided into <20 years, 20-35 years, >35 years age group, with Chi-square test at 95% confidence level used to analyze the data. The results showed that from 1.266 patients diagnosed with abortion at Ulin General Hospital Banjarmasin, a total of 37 patients were diagnosed with recurrent miscarriage. We found that the number of women who suffered recurrent miscarriage at <20 years of age wasÂ Â Â  1 (2.70%) patient, at 20-35 years of age were 21 (56.76%) patients, and at >35 years of age were 15 (40.54%) patients. Overall, a total of 16 (43,24%) patients were within the recurrent miscarriage risk factor age group while 21 (56,76%) patients were outside the risk factor age group. There was a statistically significant relation between motherâs age withÂ  the incidence of recurrent miscarriage (Ï2 = 10,6, P = 0.05).Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords: recurrent miscarriage incidence, motherâs age, Obstetric and GynecologicDepartment of Ulin General Hospital Banjarmasin